Successful pilot on Index Based Flood Insurance in Indian state of Bihar, informs policy makers and development agencies for scaling - CGIAR Research Program on Climate Change, Agriculture and Food Security (2019)
Index-based flood insurance (IBFI), relying on advanced modeling with the use of satellite data, speeded payouts to more than 11,000 flood-affected farm households, benefitting indirectly another 100,000 farmers, who learned from participating neighbors through a crowdsourcing approach.